Effect of cold atmospheric plasma versus conventional surface treatments on the bond strength between CAD-CAM zirconia and resin cement - Kamis, Gulay; Eser, Bekir (Mosher & Linder, Inc, 2023)
Purpose: To evaluate the shear bond strength of two different resin cements to zirconia after treatment with cold atmospheric pressure plasma (CAPP) and other surface modification methods. Methods: 189 specimens fabricated from Vita YZ-HT zirconia discs were divided into nine surface treatment groups: (1) Untreated (U), (2) Sandblasting (S), (3) Laser (L), (4) Plasma (P), (5) Primer (PR), (6) Sandblasting + Primer (SPR), (7) Laser + Primer (LPR), (8) Plasma + Primer (PPR), (9) Laser + Plasma + Primer (LPPR). Surface roughness (Ra) and contact angles were measured (n= 10 each), and scanning electron microscopy (SEM) and energy dispersive spectrometry (EDS) analyses were performed (n= 1 each). Specimens were cemented with RelyX Ultimate Clicker adhesive resin cement or Theracem self-adhesive resin cement. The specimens were subjected to shear bond strength (SBS) test. Modes of failure were examined under a stereomicroscope and visualized by SEM. Results: The S, PR, SPR, PPR and LPPR groups showed significantly greater Ra values than the U group. Significantly lower contact angles were observed in the S, P and L groups versus the U group. The SBS values of SPR, PPR and LPPR groups were significantly greater than those of the U group. CAPP can improve zirconia-resin cement bond strength by increasing the wettability of zirconia surfaces pretreated with the 10-methacryloyloxydecyl dihydrogen phosphate (MDP) primer.
Keywords: Nonthermal Plasma; Composite Resin; Adhesives; Primers; Argon